The Tools of the Mind curriculum for improving self‐regulation in early childhood: a sytematic review. Issue 1 (16th October 2017) - Baron, Alex; Evangelou, Maria; Malmberg, Lars‐Erik; Melendez‐Torres, G.J.
Abstract : This Campbell systematic review examines the evidence on the effectiveness of the Tools of the Mind curriculum in promoting children?s self‐regulation and academic skills, in order to inform its implementation in schools. The participants included students of all ages, gender, ethnicity, special education status, language‐learning status, and socio‐economic status. The review summarizes findings from 14 records across six studies conducted in the USA. The Tools curriculum significantly improved children?s math skills relative to comparison curricula, but the effect size was small. There are also shortcomings in the quality of evidence. Although the average effect sizes for self‐regulation and literacy favored tools compared to other approaches, the effect was not statistically significant. The evidence from the small number of included studies is mostly consistent with the evidence observed for other similar programs, but again the evidence is weak. The results for the outcome measures were not statistically significant. Plain language summary: The Tools of the Mind curriculum improves self‐regulation and academic skills in early childhood: The Tools of the Mind early childhood curriculum appear to improve children's self‐regulation and academic skills. The assessment of the tools curriculum is hampered by a lack of rigorous evidence and more research is necessary to corroborate this finding. What did the review study?: Tools of the Mind (Tools) is an early childhood education curriculum, which involves structured make‐believe play scenarios and a series of other curricular activities. Tools aims to promote and improve children's self‐regulation and academic skills by having a dual focus on self‐regulation and other social‐emotional skills in educational contexts. This review examines the evidence on the effectiveness of Tools in promoting children's self‐regulation and academic skills, in order to inform its implementation in schools. What is the aim of this review?: This Campbell systematic review examines the evidence on the effectiveness of the Tools of the Mind curriculum in promoting children's self‐regulation and academic skills, in order to inform its implementation in schools. The participants included students of all ages, gender, ethnicity, special education status, language‐learning status, and socio‐economic status. The review summarizes findings from 14 records across six studies conducted in the USA. What studies are included?: Included studies had to have used randomized controlled trials or quasi‐experimental studies and reported on one or more quantitative effect sizes regarding tools' effectiveness in self‐regulatory or academic domains. A total of 14 records across six studies were included in the review. The participants included students of all ages, gender, ethnicity, special education status, language learning status, and socio‐economic status. The studies included measured at least one of four primary outcomes and did not measure any secondary outcome. Studies that compared Tools with a business‐as‐usual or another intervention were included in the review. All included studies were conducted in the USA. What are the main results of the review?: The Tools curriculum significantly improved children's math skills relative to comparison curricula, but the effect size was small. There are also shortcomings in the quality of evidence. Although the average effect sizes for self‐regulation and literacy favored tools compared to other approaches, the effect was not statistically significant. The evidence from the small number of included studies is mostly consistent with the evidence observed for other similar programs, but again the evidence is weak. The results for the outcome measures were not statistically significant. What do the findings of this review mean?: Generally, the Tools curriculum seems to improve children's self‐regulation and academic skills. However, given the small number of included studies, as well as other methodological shortcomings, such as the high risk of bias in some of the included studies, this conclusion should be read with caution. While there is doubt as to the validity of the findings, tools' educational approach seems to be consistent with many child developmental theories and as such, should not be ruled out. There is a need to conduct more high quality research, especially about studies focused on demonstrating tools' effectiveness in promoting children's self‐regulation skills. How up‐to‐date is this review?: The review authors searched for studies published up to December 2016. This Campbell Systematic Review was published in October 2017. Executive Summary/Abstract: BACKGROUND: Tools of the Mind (Tools) is an early childhood education curriculum that aims to simultaneously promote children's self‐regulation and academic skills. Given the increasing focus on self‐regulation and other social‐emotional skills in educational contexts, Tools has become increasingly implemented in classrooms around the United States, Canada, and Chile. Despite its growing popularity, Tools' evidence base remains mixed. OBJECTIVES: The aim of this review is to synthesize the evidence on the effectiveness of the Tools program in promoting children's self‐regulation and academic skills. SEARCH METHODS: The systematic search was conducted from October 21 through December 3, 2016. The search yielded 176 titles and abstracts, 25 of them deemed potentially relevant. After full‐text screening, 14 reports from six studies were eligible for inclusion. SELECTION CRITERIA: In order to be included, a study must have had one or more quantitative effect sizes regarding Tools' effectiveness in the self‐regulatory or academic domains. Moreover, the study must have employed statistical mechanisms to control for potential confounds. Studies that compared Tools with a business‐as‐usual or another intervention were eligible for inclusion, whereas studies that did not pertain to the Tools curriculum were excluded. The reports, whether published or unpublished, could come from any national context, language, student population, or time period as long as the conditions outlined above were met. DATA COLLECTION AND ANALYSIS: All included studies classified as randomized controlled trials, though, again, quasi‐experimental studies had been eligible for inclusion. Each included study yielded effect sizes in the form of standardized mean differences. The outcomes of interest included assessor‐reported self‐regulation skills (e.g., teachers or parents rating children's self‐regulation), task‐based self‐regulation skills (e.g., children performing a self‐regulation task on a computer and receiving a score), literacy skills, and math skills. All effect sizes were interpreted as Tools' effect relative to other business‐as‐usual programs or other interventions. RESULTS: The evidence indicated statistically significant benefits for Tools children on the math pooled effect size. The other pooled effect sizes for self‐regulation and literacy favored Tools but did not reach statistical significance. AUTHORS' CONCLUSIONS: The results indicate positive yet small effects for the Tools program. Three of the four pooled effect sizes did not reach statistical significance, but all four pooled effect sizes favored Tools. The small number of included studies reduced power, which could explain the lack of statistical significance across three of the four outcome measures. By contrast, it is also possible that Tools either does not substantially influence children's self‐regulation or that the influence is too small to be detected with the current evidence base. Background